Stem Cells and Labeling for Spinal Cord Injury - Gazdic, Marina; Volarevic, Vladislav; Arsenijevic, Aleksandar; Erceg, Slaven; Moreno-Manzano, Victoria; Arsenijevic, Nebojsa; Stojkovic, Miodrag (International journal of molecular sciences, 2016)
Spinal cord injury (SCI) is a devastating condition that usually results in sudden and long-lasting locomotor and sensory neuron degeneration below the lesion site. During the last two decades, the search for new therapies has been revolutionized with the improved knowledge of stem cell (SC) biology. SCs therapy offers several attractive strategies for spinal cord repair. The transplantation of SCs promotes remyelination, neurite outgrowth and axonal elongation, and activates resident or transplanted progenitor cells across the lesion cavity. However, optimized growth and differentiation protocols along with reliable safety assays should be established prior to the clinical application of SCs. Additionally, the ideal method of SCs labeling for efficient cell tracking after SCI remains a challenging issue that requires further investigation. This review summarizes the current findings on the SCs-based therapeutic strategies, and compares different SCs labeling approaches for SCI.
Keywords: buněčný tracking; spinal cord injury; neurogeneze; nervové kmenové buňky; regenerace nervu; Animals; lidé; Nerve Regeneration; stem cell labeling; Neural Stem Cells; Spinal Cord Injuries; stem cells; Cell Tracking; Humans; poranění míchy; zvířata; Neurogenesis